Role of Human Resources in Developing Organizational Trust in Public Sector Organizations of India - Kapoor, Sneha Jha (Auckland University of Technology, 2019)
Global economy has given rise to strategic human resource management (SHRM) in recent times. On account of this, the HRM systems have been identified as one of the crucial aspects of any organization since last few decades (Robinson & Rousseau, 1994; Whitener, 1997; Searle & Dietz 2012). SHRM is in a constant need to redefine itself in order to create a competent workforce and restructure HRM systems that are on par with market demands. This has led many scholars to investigate trust as a valuable resource within organizations (Cho & Poister, 2013; Snape & Redman, 2010). Therefore, the researcher seeks to investigate how HRM contributes to the development of organizational trust in public sector organizations (PSO) of India. For this, the researcher has undertaken a multiple case study design where five Indian PSOs are selected. To highlight some of the important findings of the study, the analysis reveals that leadership practices, best practices and positive social exchange interactions in the organization create trust. The study also reveals the role of upward communication, personal relationships, and teamwork in developing trust. The contribution of this dissertation is in its ability to demonstrate the important themes such as autonomy, upward communication, policy revision, and personal relationships which were not reported in the extant literature.
Keywords: Organizational trust; Public sector; High performance work practices; Social exchange theory; Multiple case study